Technological change and cooperative technology in The Valley Morelia-Queréndaro, Michoacán, Mexico - Franco Gaona, Arturo; Cruz León, Artemio; Ramírez Valverde, Benito (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to recognize the type of agriculture that has been practiced in the region, the technology used, the changes that have been taken and, the implications that were triggered by adopting new technologies; from the use of the yoke to the tractor, it describes the agricultural technology used by three valley communities of Queréndaro, Morelia, based on the instrument, technique and knowledge used since its formation. This research was conducted during 2009 and 2010. For this study we used the key informant method with a semi-structured interview and a transept. We found that, the cultivation practices were made through the force of the humans, the oxen, horses and mules, plus the use of the tractor and the application of technology packages, whose main promoter was the government, through the implementation of public policies: particularly in irrigated areas, and the abandonment of the bean crop as a result of the use of herbicides. In the irrigated area of mechanization it made its presence using the tractor and a trend towards the cultivation of fodders, which are integrated to livestock as a production system. The power of the tractors in the region, in ‘horsepower’ (HP), exceeds by almost three times that required for the amount of the arable-land, which implies an under-utilization of labor capacity of the tractors, used for sowing by their owners or through maquila.
Keywords: communal agricultural history; farmer; maquila costs; traditional agricultural technology; use of tractors